Management of Company-Owned Assets in the Regional Government-Owned Enterprise of DKI Jakarta Province - Irsyad, Muammar; Karunia, Luki; Sutrisno, Edy (Ilomata International Journal of Management, 2025)
The management of regional assets is critical for promoting good governance and accurate financial reporting, as outlined in Minister of Home Affairs Regulation Number 19 of 2016. Despite this, Perumda Pembangunan Sarana Jaya faces significant challenges in asset management, including discrepancies in data recording, inadequate human resources, and a lack of proper documentation for asset movements. These issues hinder the transparency and accountability necessary for effective governance. This is a descriptive qualitative research. Data is collected through primary sources, such as interviews with key personnel involved in asset management, and secondary sources, including document analysis of asset management procedures. The asset management at Perumda Pembangunan Sarana Jaya faces significant challenges due to manual bookkeeping, inconsistent asset classification and coding, and the absence of standardized procedures. Inventory management is also ineffective, with outdated regulations and uncoordinated data between divisions. To address these issues, it is recommended that the company improves coordination, establishes standardized asset categorization and coding systems, and implements a modern, technology-based information system for more efficient asset tracking and reporting. Additionally, data reconciliation between divisions and consistent monitoring by leadership are crucial for accurate and transparent asset management.